Glycosyl Mobile Radical Structures of Folic Acid Receptors Impact the Internalization of Functionalized Folate Amphiphilic Alternating Copolymer in Cancer Cells - Emilyn B. Aucoin; Elizabeth Skapinker; Abdulrahman M. Yaish; Yunfan Li; Haley L. Kombargi; Daniel Jeyaraj; Pankaj Garg; Nicole Mendonza; Cecile Malardier-Jugroot; Myron R. Szewczuk (Receptors)
Folate receptor alpha (FRα) is a glycosylphosphatidylinositol (GPI) membrane-anchored protein containing three N-glycosylated residues at the N47, N139, and N179 termini. These glycosylation sites have been reported to be crucial for the receptor’s structural integrity and its ability to bind and internalize FA. Here, we investigated the role of FRα glycosylation in the binding and internalization efficacy of FA–DABA–SMA in pancreatic PANC-1 cancer cells. There is a strong association of the FA copolymer with FRα with a Pearson coefficient R-value of 0.7179. PANC-1 cancer cells were pretreated with maackia amurensis lectin II (MAL-2), sambucus Nigra lectin (SNA-1), peanut agglutinin (PNA), and wheat germ agglutinin lectin (WGA) at different doses followed by 20 kDa and 350 kDa FA–DABA–SMA loaded with coumarin 153 (C153). Increasing the dosage of MAL2, SNA-1, PNA, and WGA concomitantly and significantly increased the internalization of C153-loaded FA–DABA–SMA in the cells. The half maximal effective lectin concentrations (EC50) to induce cellular internalization into the cytoplasm of the lectins for MAL-2 were 35.88 µg/mL, 3.051 µg/mL for SNA-1, 7.883 µg/mL for PNA, and 0.898 µg/mL for WGA. Live cell imaging of the internalization of 20 kDa and 350 kDa FA copolymers indicated an aggregation of 350 kDa copolymer with FRα in the cytoplasm. In contrast, the 20 kDa FA copolymer remained in the membrane. The data indicate for the first time that the mobile positions of the glycosyl radical groups and the receptor tilt in generating steric hindrance impacted the individual FRα receptors in the binding and internalization of 350 kDa FA–DABA–SMA in cancer cells.